Spectrum of Permanent's Values and Its Extremal Magnitudes in Λn3 and Λn(α, β, γ). (17th November 2013) - Shevelev, Vladimir
Abstract : LetΛ n k denote the class of( 0, 1 ) square matrices containing in each row and in each column exactlyk 1's. The minimal value ofk, for which the behavior of the permanent inΛ n k is not quite studied, isk = 3 . We give a simple algorithm for calculation of upper magnitudes of permanent inΛ n 3 and consider some extremal problems in a generalized classΛ n ( α, β, γ ), the matrices of which contain in each row and in each column nonzero elementsα, β, andγ andn - 3 zeros.